1992
DOI: 10.1507/endocrj1954.39.153
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Effect of Pituitary Adenylate Cyclase Activating Polypeptide 38 (PACAP 38) on the Secretion of Luteinizing Hormone (LH) in Male Rats.

Abstract: Abstract.In was ineffective. The time course pattern of LH release by intraatrial injection and that by icy injection was similar, but the LH levels increased by intraatrial injection were much higher than that by icv injection. Intraatrial administration of VIP had almost no effect on LH release. These findings suggested that PACAP 38 stimulates LH release in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 13 publications
2
33
1
Order By: Relevance
“…There are two main explanations for the lack of high levels of LH expected in primary hypogonadism: (i) residual testosterone, although low, could still be high enough to ensure negative pituitary feedback, and (ii) the normal levels of LH, given the low testosterone values, are actually inappropriately low, giving credence to the concept that PACAP may stimulate LH release in vivo as suggested in ref. 18. In this context, the absence of PACAP prevents the appropriate and expected surge in LH levels in the context of testosterone deficiency in PACAP Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…There are two main explanations for the lack of high levels of LH expected in primary hypogonadism: (i) residual testosterone, although low, could still be high enough to ensure negative pituitary feedback, and (ii) the normal levels of LH, given the low testosterone values, are actually inappropriately low, giving credence to the concept that PACAP may stimulate LH release in vivo as suggested in ref. 18. In this context, the absence of PACAP prevents the appropriate and expected surge in LH levels in the context of testosterone deficiency in PACAP Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 97%
“…The neuropeptide PACAP has been implicated in regulation of testosterone level in cultured Leydig cells (20)(21)(22)29). It has also been shown to potentially enhance the release of LH in vivo (18). PACAP, acting on PAC1 receptors that efficiently enhance cAMP production and intracellular calcium mobilization was shown to directly interact with many cell types, such as gonadotrope, Leydig, germ, and Sertoli cells (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with this possibility, we have previously described that estradiol and progesterone modulate LH secretion from gonadotrophs in response to other agonists that activate phospholipase C such as endothelin (36). The fact that gonadal steroids exert stimulatory and inhibitory actions on PACAP-stimulated LH release might explain the controversial data of in vivo studies on the ability of PACAP to induce gonadotropin secretion (19,(37)(38)(39).…”
Section: European Journal Of Endocrinology (1999) 140mentioning
confidence: 99%
“…VPAC-1 and VPAC-2 bind equally PACAP and VIP, and are almost exclusively coupled to adenylate cyclase (Spengler et al 1993, Rawling & Hezareh 1996, Jaworski & Proctor 2000. The expression of PACAP and its receptors can be found in many tissues, including hypothalamus, pituitary, testis and ovary (Vaudry et al 2000), and the role of PACAP in reproduction has been suggested by studies showing its involvement in the synthesis and release of gonadotropins in pituitary cells in vivo and in vitro (Hart et al 1992, Osuga et al 1992, Perrin et al 1993.…”
Section: Introductionmentioning
confidence: 99%